Mindfulness, Spirituality, and Quality of Life among Cancer Survivors Undergoing Chemotherapy: Three-Month Observational Studies in Indonesia - Mulyono, Wastu Adi; Chen, Hsing-Mei (Fakultas Ilmu-ilmu Kesehatan, 2023)
Cancer survivors’ population has continued to increase. However, survivorship remains challenging for most. Further development of new strategies to combat stress during survivorship was in demand. While religious-spiritual aspects were available as potential resources. A prospective study contributed 274 cancer survivors was conducted. Instruments included the Freiberg Mindfulness Inventory, Functional Assessment of Chronic Illness Therapy - Spiritual Well-Being, Perceived Stress Scale, and the Brief World Health Organization Quality of Life. Three-time points data were set, baseline, one month, and three months. Data were analyzed using repeated-measures ANOVA. The results showed that the mean age of the 274 cancer survivors was 48.97 (11.85) years old with a survivorship period of 1.35 years. Series data obtained from three points measurements each variable were mindfulness 34.15, 33.12, and 40.41; spirituality 33.40, 30.87, and 32.56, stress 20.31, 21.56, and 19.48, and quality-of-life 61.49, 55.71, 63.84, respectively. In conclusion, cancer survivors experienced fluctuating levels of mindfulness and spirituality, stress, and quality of life for three months of observations. However, the natural improvement of mindfulness, spirituality, stress, and quality of life improved in month three.